MO746: Marinobufagenin, Left Ventricular Geometry and Cardiac Dysfunction in End-Stage Kidney Disease Patients. (3rd May 2022) - Patella, Gemma; Presta, Pierangela; De Rosa, Salvatore; Greco, Marta; Crugliano, Giuseppina; Sabatino, Jolanda; Cianfrone, Paola; Andreucci, Michele; Indolfi, Ciro; Foti, Daniela; Coppolino, Giuseppe; Bolignano, Davide
Abstract: BACKGROUND AND AIMS: Left ventricular hypertrophy (LVH) is remarkably prevalent among end-stage kidney disease (ESKD) on chronic dialysis and has a strong prognostic value for adverse outcomes. In experimental models, the endogenous cardiotonic steroid Marinobufagenin (MBG) promotes cardiac hypertrophy and accelerates uremic cardiomyopathy. In this study, we investigated the possible relationships between MBG, LV geometry and cardiac dysfunction in the clinical setting of ESKD. METHOD: Plasmatic MBG was measured in 46 prevalent ESKD patients ( n  = 30 HD, n  = 16 PD) together with a thorough laboratory, clinical, bioimpedance and echocardiography assessment. Different patterns of LV geometry were defined by left ventricular mass index (LVMi) and ventricular morphology. Diastolic dysfunction was diagnosed by the ASE/EACVI criteria. RESULTS: MBG levels were significantly higher in ESKD patients than in healthy controls (0.89 ± 0.45 versus 0.59 ± 0.19 nnmol/L; P = 0.001) and more elevated in PD than in HD (1.09 ± 0.22 versus 0.78 ± 0.55 nnmol/L; P = 0.02). At univariate analysis, MBG was directly correlated with LVMi ( R  = 0.63; P < 0.001), LAVi ( R  = 0.57; P < 0.001), E / e ' ( R  = 0.57; P < 0.001), RAVi ( R  = 0.42; P = 0.01) and NT-proBNP ( R  = 0.37; P = 0.01), whereas a significant inverse correlation was observed with extracellular volume at bioimpedance ( R =–0.33; P = 0.02). At multivariate analyses, E / e ' (β=0.38; P = 0.009) and LVMi (β = 0.42; P = 0.02) remained the sole independent predictors of MBG. A statistically significant trend in MBG levels ( p =0.01) was noticed across different patterns of LV geometry, with the highest values found in eccentric LVH (Fig. 1 ). MBG levels were higher in the presence of diastolic dysfunction (P = 0.01) and this substance displayed a remarkable diagnostic capacity in distinguish patients with normal LV geometry, LV hypertrophy and, particularly, eccentric LVH (AUC 0.888; P < 0.0001) and diastolic dysfunction (AUC 0.79; p =0.001). CONCLUSION: Deranged plasma MBG levels in ESKD patients on chronic dialysis may reflect alterations in LV structure and function. MBG may thus candidate as a novel biomarker for improving cardiac assessment in this high-risk population.